2020
DOI: 10.1097/scs.0000000000007120
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Patient Satisfaction of the Postoperative Nasal Topographic, Demographic, and Functional Results of Open and Closed Septorhinoplasty Techniques

Abstract: Aim: To evaluate the contribution to patient satisfaction of the newly reshaped topographic anatomy of the nose, demographic, and functional results in the postoperative period of septorhinoplasty surgery. Method: A total of 370 patients applied with open and closed septorhinoplasty techniques for various reasons were grouped according to the postoperative Rhinoplasty Outcome Evaluation (ROE) Scale results; Group 1 (open rhinoplasty satisfied group, ROE !12 points, n:194), Group 2 (open rhinoplasty dissatisfie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Many studies[ 21 22 23 ] concluded insignificant differences in Nasal Obstruction Symptom Evaluation (NOSE) score improvement, aesthetic outcomes and psychosocial distress levels with regard to rhinoplasty technique (open vs. closed). Kosins[ 24 ] in a study of 162 patients stated that open and closed approaches based on the tip and dorsal deformities have different indications: closed is preferred with thin skin, little dorsal modification, minimal tip deformities and over projected noses, whereas open is preferred where extensive dorsal modification is required, severe septal deviations, complex tip deformities and tip augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies[ 21 22 23 ] concluded insignificant differences in Nasal Obstruction Symptom Evaluation (NOSE) score improvement, aesthetic outcomes and psychosocial distress levels with regard to rhinoplasty technique (open vs. closed). Kosins[ 24 ] in a study of 162 patients stated that open and closed approaches based on the tip and dorsal deformities have different indications: closed is preferred with thin skin, little dorsal modification, minimal tip deformities and over projected noses, whereas open is preferred where extensive dorsal modification is required, severe septal deviations, complex tip deformities and tip augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Metin and Avcu evaluated the ROE scale in both open and closed septorhinoplasty performed on 370 patients and concluded that in open septorhinoplasty 194 patients reached an ROE ≥12 whereas only 23 with ROE <12 points (ratio 16:1),[ 11 ] while in closed septorhinoplasty 137 patients with ROE ≥12 and 16 with ROE <12 points (ratio 8:1), apparently suggesting that open surgery resulted in a higher outcome performance. [ 11 ] The conclusions held by the authors, using also the functional scale known as the Nasal Obstruction Symptom Evaluation (NOSE), assessed that the aesthetic component affecting the nasal topographic satisfaction was the nasal tip. However, they did not succeed in confirming the purported correlation between low satisfaction with surgical approach and aesthetic outcome in the few groups of patients with post-operative low ROE.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not succeed in confirming the purported correlation between low satisfaction with surgical approach and aesthetic outcome in the few groups of patients with post-operative low ROE. [ 11 ] Therefore, NOSE alone might not be particularly suitable to assess outpatients’ satisfaction, when undergoing rhinoplasty in ASCs.…”
Section: Introductionmentioning
confidence: 99%